Analyzing the impact of non-participation in the FIFA World Cup Qatar 2022 on LaLiga players' physical performance - Reverte-Pagola, G.; Pecci, J.; del Ojo-López, J. J.; Del Campo, R. L.; Resta, R.; Feria-Madueño, A. (Frontiers in Sports and Active Living, 2024)
Background: Monitoring external load demands in soccer is crucial for optimizing performance and reducing injury risk. However, events like the FIFA World Cup Qatar 2022 and unexpected interruptions can disrupt load management strategies. Understanding the impact of such events on player performance is essential for effective training and recovery strategies.